Cell-Cycle Protein Expression in a Population-Based Study of Ovarian and Endometrial Cancers - Felix, Ashley S.; Sherman, Mark E.; Hewitt, Stephen M.; Gunja, Munira Z.; Yang, Hannah P.; Cora, Renata L.; Boudreau, Vicky; Ylaya, Kris; Lissowska, Jolanta; Brinton, Louise A.; Wentzensen, Nicolas (Frontiers in Oncology, 2015)
Aberrant expression of cyclin-dependent kinase (CDK) inhibitors is implicated in the carcinogenesis of many cancers, including ovarian and endometrial cancers. We examined associations between CDK inhibitor expression, cancer risk factors, tumor characteristics, and survival outcomes among ovarian and endometrial cancer patients enrolled in a population-based case control study. Expression (negative vs. positive) of three CDK inhibitors (p16, p21, p27) and ki67 was examined with immunohistochemical staining of tissue microarrays. Logistic regression was used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for associations between biomarkers, risk factors, and tumor characteristics. Survival outcomes were available for ovarian cancer patients and examined using Kaplan-Meier plots and Cox proportional hazards regression. Among ovarian cancer patients (n=175), positive p21 expression was associated with endometrioid tumors (OR=12.22, 95% CI=1.45-102.78) and higher overall survival (log-rank p=0.002). In Cox models adjusted for stage, grade, and histology, the association between p21 expression and overall survival was borderline significant (hazard ratio=0.65, 95% CI=0.42-1.05). Among endometrial cancer patients (n=289), positive p21 expression was inversely associated with age (OR ≥ 65 years of age=0.25, 95% CI=0.07-0.84) and current smoking status (OR: 0.33, 95% CI 0.15, 0.72) compared to negative expression. Our study showed heterogeneity in expression of cell-cycle proteins associated with risk factors and tumor characteristics of gynecologic cancers. Future studies to assess these markers of etiological classification and behavior may be warranted.